Social Bonds and Latino/A Victimization: An Examination of Mediating and Moderating Effects - Lopez, Kristina M. (Victims & offenders, 2022)
Studies of Latino/a/x crime and victimization have proliferated in recent years confirming three main empirical realities: race and ethnicity remain consistently linked to criminological outcomes, the foreign-born are significantly less likely to report either crime or victimization, and nativity status (i.e., foreign-born or native-born) is associated with crime and victimization, even after controlling for germane covariates. The current study attempts to expand on this literature by examining the mediating and moderating effects of social bonds on nativity status in predicting violent victimization. Using data from the Add Health study, we estimate a series of regression and SEM models to assess if social bonds mediate or moderate the effect of nativity on self-reported victimization. Results indicate that native-born Latinos were significantly more likely to be victimized compared to their foreign-born counterparts, though the effect of nativity was reduced to marginal significance after inclusion of the mediating and moderating variables in the full models. Contrary to expectations, native-born and foreign-born Latinos did not differ significantly in terms of social bonds with parents (attachment and time spent with parents) but the foreign-born were significantly more likely to be closely monitored by their parents which partially mediated the association between nativity and violent victimization.